Potential and Utilization Rate of Indian Scad (Decapterus russelli) Landed at UPTD Fishery Port Region I, Carocok Tarusan, West Sumatra Province - Ukhwatul, Vify; Brown, Arthur; Zain, Jonny (Jurnal Perikanan dan Kelautan, 2025)
The utilization of Indian scad (Decapterus russelli) in Carocok Tarusan has made an important contribution to fishing activities, but data on the potential and rate of utilization are limited. The research aims to determine the potential and level of utilization of indian scad (Decapterus russelli) landed at UPTD Fishery Port Region I, Carocok Tarusan, West Sumatra Province. The research was conducted in December 2024 using secondary data from the institution on catch and fishing efforts for 2019-2023. Methods used are Catch Per Unit Effort (CPUE) and surplus production models of Schaefer and Fox to estimate the maximum sustainable yield (MSY) and optimum fishing effort (f-optimum). According to the analysis results, the Fox model is the most suitable model to describe the stock status and management of indian scad in this region. MSY was estimated at 234,653.74 kg/year with an optimum effort of 1,902 trips/year. Total allowable Catch (TAC) was 187,722.99 kg/year. The average utilization rate was 97%, which shows that the Indian scad stock is fully exploited. Meanwhile, the average level of effort at 110% showing that fishing effort exceeds the optimum level, meaning that more careful management is needed to ensure the sustainability of the stock